Spontaneous cerebrospinal fluid rhinorrhea associated with chronic renal failure - Case report - Ozveren, MF; Kaplan, M; Topsakal, C; Bilge, T; Erol, FS; Celiker, H; Uchida, K (Japan Neurosurgical Soc, 2001)
A 39-year-old woman was admitted with complaints of headache and nasal discharge on the left for 3 months which was later on proved to be cerebrospinal fluid (CSF). Neurological examination found no abnormalities except bilateral papilledema. Neuroinmaging demonstrated enlargement of the lamina cribrosa foramina through which the olfactory nerves pass, as well as empty sella and cerebral cortical atrophy. Bone mineral densitometry showed osteopenia. CSF Ca++ and blood parathyroid hormone levels were elevated. CSF pressure was 280 mmH(2)O. Bilateral frontal craniotomy was performed to expose the anterior fossa. Foraminal enlargement at the lamina cribrosa was confirmed, and islands of extraosseous calcifications on the arachnoid membrane were identified. The base of the anterior fossa was repaired intradurally with fascial graft and fibrin glue on both sides. No CSF leakage was noted at 1-year follow up. Spontaneous CSF leakage probably resulted from enlargement of the foramina at the lamina cribrosa due to Catt mobilization from bones and pseudotumor cerebri not to the extent of hydrocephalus caused by poor CSF absorption at the arachnoid granulations obliterated by extra-osseous calcareous accumulation.
Keywords: cerebrospinal fluid; chronic renal failure; empty sella; spontaneous rhinorrhea; pseudotumor cerebri